Gene regulation by the lysine demethylase KDM4A in Drosophila. - Crona, F.; Dahlberg, O.; Lundberg, L.E.; Larsson, J.; Mannervik, M. (Developmental Biology, 2013)
Lysine methylation of histones is associated with both transcriptionally active chromatin and with silent chromatin, depending on what residue is modified. Histone methyltransferases and demethylases ensure that histone methylations are dynamic and can vary depending on cell cycle- or developmental stage. KDM4A demethylates H3K36me3, a modification enriched in the 3' end of active genes. The genomic targets and the role of KDM4 proteins in development remain largely unknown. We therefore generated KDM4A mutant Drosophila, and identified 99 mis-regulated genes in first instar larvae. Around half of these genes were down-regulated and the other half up-regulated in dKDM4A mutants. Although heterochromatin protein 1a (HP1a) can stimulate dKDM4A demethylase activity in vitro, we find that they antagonize each other in control of dKDM4A-regulated genes. Appropriate expression levels for some dKDM4A-regulated genes rely on the demethylase activity of dKDM4A, whereas others do not. Surprisingly, although highly expressed, many demethylase-dependent and independent genes are devoid of H3K36me3 in wild-type as well as in dKDM4A mutant larvae, suggesting that some of the most strongly affected genes in dKDM4A mutant animals are not regulated by H3K36 methylation. By contrast, dKDM4A over-expression results in a global decrease in H3K36me3 levels and male lethality, which might be caused by impaired dosage compensation. Our results show that a modest increase in global H3K36me3 levels is compatible with viability, fertility, and the expression of most genes, whereas decreased H3K36me3 levels are detrimental in males.